Predictors of success in selective laser trabeculoplasty for primary open angle glaucoma in Chinese - Lee, Jacky WY (Dove Medical Press, 2014)
PURPOSE: To determine the predictors of success for adjuvant selective laser trabeculoplasty (SLT) in Chinese primary open angle glaucoma (POAG) patients. METHODS: This prospective study recruited Chinese subjects with unilateral or bilateral POAG currently taking medication to reduce intraocular pressure (IOP). All subjects received a single session of 360° SLT treatment and continued their medications for 1 month. SLT success was defined as IOP reduction ≥20% at 1 month. The following covariates were analyzed in both groups via univariate and multivariate analyses: age, sex, lens status, initial IOPs, post-SLT IOPs, number and type of medications, SLT shots and energy, and pre-SLT investigations. RESULTS: In 51 eyes of 33 POAG subjects, the success rate of SLT was 47.1%. Certain groups of patients were associated with greater success using univariate analysis. These groups included the following: older age (coefficient =0.1; OR: 1.1; P=0.0003), a higher pre-SLT IOP (coefficient =0.3; OR: 1.3; P=0.0005), using four types of antiglaucoma medication (coefficient =2.1; OR: 8.4; P=0.005), a greater degree of spherical equivalent (coefficient =2.1; OR: 8.4; P=0.005), and the use of a topical carbonic anhydrase inhibitor (coefficient =1.7; OR: 6.0; P=0.003). None of the covariates were significant using multivariate analysis. CONCLUSION: Older age, a higher pretreatment IOP, using multiple antiglaucoma medications especially topical carbonic anhydrase inhibitor, and higher refractive errors were associated with greater SLT success.